Adapted hepatitis C virus clone infects innate immunity-deficient mouse hepatocytes with minimal human HCV entry factors - Julie Ann Sheldon; Melina Winkler; Qinggong Yuan; Nicola Frericks; Richard John Phillip Brown; Csaba Miskey; Natascha Gödecke; Sara Behme; Katharina Rox; Giorgia Mysegades; Florian Vondran; Dagmar Wirth; et al. (JHEP Reports)
Background & Aims: Hepatitis C virus (HCV) has a narrow species tropism and cannot infect mice. To understand HCV species tropism and to develop better animal models, we adapted HCV to infect mouse cells deficient in innate immunity and with minimal human HCV host factors. Methods: HCV was adapted via passaging an HCV infectious virus clone several times in human hepatoma cells, mouse liver cells, and eventually primary mouse hepatocytes deficient in innate immunity and ectopically expressing human occludin and human CD81. Using RNAseq the sequence of the adapted virus was analyzed, and several clones were generated to study replication and infection kinetics as well as neutralization assays in several human/mouse cell lines and primary hepatocytes from human, mouse, and macaques. Results: Accumulation of 35 non-synonymous and 66 synonymous mutations correlated with >1,000-fold enhanced production of infectious progeny from primary mouse hepatocytes. These mutations did not confer drug resistance or evasion from innate immunity. They did not enhance fitness in human or macaque hepatocytes. We show that non-synonymous mutations are necessary and sufficient for adaptation, and that changes to the glycoproteins are not essential. Mutations outside of viral envelope proteins enhanced specific infectivity and facilitated viral spread in murine cells. Conclusions: This study reveals key viral factors governing HCV species tropism. The mouse-adapted HCV opens up possibilities for the development of animal models to analyze HCV pathogenesis, immune control, and vaccine development. Impact and implications: This work demonstrates the feasibility in principle of HCV adaptation to replication in and infection of non-human cells. This is made possible by a manageable number of non-synonymous mutations and opens up new ways to elucidate the principles of HCV species tropism and to develop important animal models for HCV research in the long term.